Marketing the history of Kediri through the integrated website "kediri kita.com" - Nilasari, Nevia Octi; Prayogo, Bangun; Sanjaya, Rendra T; Qoyyim, Ibnu (Prosiding Seminar; 2020: 2020 International Conference of Interdisciplinary SciencesDO - 10.32503/prosidingseminar.v0i0.24, 2020)
the purpose of this study is design of website information to guide people find information of historical destination in Kediri. Kediri has a long history since the Hinduism-Buddhism era and Also the era of Dutch-Portuguese colonialism, it makes Kediri has many traces of history can still be seen today such as the temple of the kingdom of Kadiri, the kelud, and old Dutch buildings architecture such as Kediri station, the old bridge and many more. This makes a lot of tourists visiting Kediri, the tourists Generally seek many information through the Internet, but the information Obtained Generally unorganized, this is the reason for the developing a website that Provides a wide information about the history of Kediri, Routes of travel and hotels in Kediri in a single website. The method used content analysis and observation. An observation was conducted on the websites, literatures, and secondary of data on the internet about Kediri. The result has website that contains information of historical object in Kediri.